(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The regulation of GMOs lies within the framework of a multiplicity of principles and interests at stake ranging from food security to the fight against hunger and malnutrition, to healthy food, sustainable development, biodiversity and food sovereignty. From a comparative perspective, a circulation of legal models, in particular the European one based on the precautionary principle, is inserted in the context of the existing legal pluralism. However, this phenomenon raises questions, on the one hand, with respect to the dynamics of international trade with more permissive legal systems such as the United States, on the other, with regard to the limited effectiveness of the application of this model in some systems such as the Chinese one. As regards the recognition of intellectual property rights, the case of foods obtained from CRISPR shows the difference in regulatory approaches also with respect to patentability on both sides of the Atlantic. Lasty, with regard to ensuring the transparency and traceability of GMO products, the new option of "techno-regulation" is emerging through technologies based on distributed registers such as the blockchain.